Ethical Judgement Competence in Geographical Education – Theoretical Foundations for the Design of a Competence Model - Meyer, Christiane; Felzmann, Dirk (Journal of Geography Education, 2010)
Valuation is one of the six areas of competences, which are proclaimed in the Educational Standards in Geography for the Intermediate School Certificate (DGfG 2008). In this article some relevant theoretical considerations about ethical judgement in geography class are outlined. This includes aspects from philosophy, especially concerning the structure of an ethical argument, from developmental psychology and from geographical education. Competence models for ethical judgement in biological education are presented and possible implications for a competence model in geographical education are discussed.